1964
DOI: 10.1111/j.1365-2389.1964.tb02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols in Plant, Humus, and Soil

Abstract: The leuco-anthocyanin and tannin contents of green leaves of several species collected at mull sites have been compared with those collected at mor sites. Species growing under mor conditions usually contain greater amounts of both than the same species under mull. By growing a number of plants in sand it has been shown that this high content of polyphenolic substances can be associated with lack of nitrogen or of phosphorus. I Present address:quantity of olyphenolic substances in fresh beech K eaves obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1964
1964
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Além do efeito biotóxico, a formação de complexos estáveis de Al-MO torna a MO mais resistente à oxidação, preservando-a, como reportado por Volkoff et al (1984), Mendonça (1995) e Benites et al (1999), em solos tropicais e subtropicais. Em condições de elevado Al trocável, as plantas produzem maior quantidade de compostos fenólicos, reduzindo, mais ainda, a sua degradabilidade (Davies et al, 1964).…”
Section: Atributos Químicos E Físicos Dos Solosunclassified
“…Além do efeito biotóxico, a formação de complexos estáveis de Al-MO torna a MO mais resistente à oxidação, preservando-a, como reportado por Volkoff et al (1984), Mendonça (1995) e Benites et al (1999), em solos tropicais e subtropicais. Em condições de elevado Al trocável, as plantas produzem maior quantidade de compostos fenólicos, reduzindo, mais ainda, a sua degradabilidade (Davies et al, 1964).…”
Section: Atributos Químicos E Físicos Dos Solosunclassified
“…Segundo Riffaldi & Schnitzer (1972), os radicais semiquinona são formados pela remoção oxidativa de hidrogênio dos grupos OH de fenóis; portanto, a concentração de fenóis no material de origem pode influenciar a concentração de spins das substâncias húmicas formadas a partir deste. Condições de distrofismo e presença de alumínio solúvel podem influenciar mecanismos fisiológicos de produção de polifenóis, como taninos e flavonóides, pela cobertura vegetal, alterando a qualidade da manta orgânica (Davies et al, 1964). Traghetta et al (1997) encontraram uma concentração de radicais livres em amostras de manta orgânica do Campos de Altitude cerca de dez vezes superior à registrada nas amostras da manta orgânica sob mata.…”
Section: Espectroscopia De Ressônancia Paramagnética Eletrônica (Rpe)unclassified
“…Collagen tanned with tannic acid, chestnut wood, and sumac tanning extracts (hydrolysable tannins) is less resistant to the attack of trypsin than collagen tanned with mimosa, quebracho, and gambier extracts (condensed tannins) (Gustavson, 1956;Lipsitz et al, 1949). The detection of catechins in beech leaves and leuco-anthocyanins in oak, beech, and birch (Davies et al 1964) suggests that the tannins in the gelatin-tannin complexes used in the present investigation were of the condensed variet . A paper chromatographic examinabeech leaves has shown that at least fifteen olyphenols are present…”
Section: Discussionmentioning
confidence: 93%